IMPROVING STUDENTS’ SPEAKING ACHIEVEMENT THROUGH THINK-PAIR-SHARE TECHNIQUE - Dinda Fatariq Andika Lubis and Lidiman S.M. Sinaga (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study attempts to improve students’ speaking achievement through think-pair-share technique by conducting action research method. The subject of this study was XI-IPA 1’s students which consisted of 36. This study was conducted in two cycles and each cycle consisted of three meetings. The instruments for collecting data were quantitative (speaking test) and qualitative data (diary notes and observation sheet). Based on the data analysis from each activity, there is a significant achievement in cycle I and cycle II. In the speaking test, the students’ score kept improving in every test, the mean of the students’ score in cycle I was 66.11 and cycle II was 73.27. Based on diary notes and observation sheet, it was found that teaching learning process ran well. The result of the research showed that by applying think-pair-share technique in teaching English, especially in speaking is effective to improve the students’ speaking achievement.